(untitled) (Research, Society and Development, 2021)
This study aimed to identify, in the scientific literature, the multidisciplinary care that is offered to patients in palliative care hospitalized in intensive care units. An integrative literature review was carried out, with the inclusion of original articles that answered the research question, without limitation of year and language. As a result, a total of nine articles were included for the synthesis of the studies, being mostly researches of Brazilian origin and of a qualitative nature. The articles analyzed enabled the vision of care from different professional categories, which focused on physical comfort actions, such as pain relief and other symptoms, followed by support for the emotional sphere. Actions to support families appeared less frequently in the studies, and religious support was present. It was possible to realize that the multidisciplinarity needs to be encouraged in such environments, providing, in such way, a more holistic care to the patients and family.